Desain Sistem Informasi Akuntansi Penggajian Untuk Optimalisasi Efesiensi dan Akurasi Pengolahan Data Pada PT. Omni Metro Guardia Jakarta - Widya Apriliah; Marlina Indrastari; Cahya Adi Ramadhani; Jennieka Salsabila; Ratnawati (PROFITABILITAS, 2025)
The development of information technology requires companies to improve the efficiency and accuracy of accounting processes in payroll management. However, the fact is that some companies do not fully utilize technology for company operations, including PT Omni Metro Guardia, which often faces various challenges in terms of efficiency and accuracy. The salary calculation process at PT Omni Metro Guardia shows that the system used is still not fully computerized. This results in the payroll process taking a long time, disorganized data storage, and difficulty accessing employee data. This research aims to design a payroll accounting information system to improve efficiency and accuracy in the process of managing employee payroll at PT Omni Metro Guardia which is equipped with tax calculations and automatic cash out reports. In this design, the design thinking method is used to create innovative, effective, accurate system solutions, according to user needs which include empathize, define, ideate, prototype, and test stages. The result of this research is the implementation of an automated payroll accounting information system that is able to speed up the salary calculation process, store digital data and increase data accessibility. With this system, it is hoped that it can provide a comprehensive solution to PT. Omni Metro Guardia to overcome existing problems and improve the efficiency of the system.